Rest-Only Myocardial CT Perfusion in Acute Chest Pain. Issue 11 (November 2015) - Thomas, Dustin M.; Larson, Christopher W.; Cheezum, Michael K.; Villines, Todd C.; Branch, Kelley R.; Blankstein, Ron; Cury, Ricardo C.; Slim, Ahmad M.
Abstract : Objectives: Cardiac computed tomography perfusion (CTP) using stress testing is an emerging application in the field of cardiac computed tomography. We evaluated patients with acute chest pain (CP) in the emergency department (ED) with evidence of obstructive coronary artery disease (CAD), defined as >70% stenosis on coronary computed tomography angiography (CCTA) and confirmed by invasive coronary angiography (ICA), to evaluate the applicability of resting CTP in the acute CP setting. Methods: From January to December 2013, 183 low-intermediate risk symptomatic patients with negative cardiac biomarkers and no known CAD underwent a rapid CCTA protocol in the ED. Of these, 4 patients (1.4%) had obstructive CAD (≥70% stenosis) on CCTA confirmed by ICA. All 183 CCTA studies were evaluated retrospectively with CTP software by a transmural perfusion ratio (TPR) method with a superimposed 17-segment model. A TPR value <0.99 was considered abnormal based on previously published data. Results: A total of four patients were included in this pilot analysis. The duration from resolution of CP to performance of CCTA ranged from 1.6 to 5.0 hours. Three patients underwent revascularization, two with percutaneous coronary intervention (PCI) and one with coronary artery bypass grafting. The fourth patient was managed with aggressive medical therapy. Two patients had multivessel obstructive CAD and two patients had single-vessel CAD. The first patient underwent CCTA 5 hours after resolution of CP symptoms. CCTA demonstrated noncalcified obstructive CAD in the mid-LAD and mid-right coronary artery. ICA showed good correlation by quantitative coronary assessment (QCA) in both vessels and the patient underwent PCI. CTP analysis demonstrated perfusion defects in the LAD and right coronary artery territories. The second patient underwent CCTA 1.6 hours after resolution of CP symptoms with findings of obstructive ostial left main CAD. ICA confirmed obstructive left main CAD by QCA and intravascular ultrasound. The patient underwent revascularization with coronary artery bypass grafting. CTP demonstrated perfusion defects in the anterior and lateral wall segments. The third patient was evaluated for CP in the ED with CCTA demonstrating single-vessel CAD 10 hours after resolution of symptoms with findings of a noncalcified obstructive stenosis in the mid-LAD. The patient subsequently underwent ICA demonstrating good correlation to the CCTA findings in the LAD by QCA. CTP analysis revealed perfusion defects in LAD territory. He was successful treated with PCI. The final patient underwent CCTA 5.4 hours following resolution of CP with the finding of an intermediate partially calcified stenosis in the distal LAD. ICA was performed, with fractional flow reserve demonstrating a hemodynamically insignificant distal LAD at 0.86. CTP detected a perfusion defect in the LAD territory. Conclusions: When positive, rest CTP may have value in the risk stratification of patients presenting to the ED with nontraumatic acute CP. Abstract : Cardiac computed tomography perfusion (CTP) using stress testing is an emerging application in the field of cardiac CT. We evaluated patients with acute chest pain in the emergency department with evidence of obstructive coronary artery disease, defined as >70% stenosis on coronary CT and confirmed by invasive coronary angiography, to evaluate the applicability of resting CTP in the acute chest pain setting without vasodilator challenge.